VALIDASI TERHADAP KELAYAKAN PRODUK VIRTUAL LABORATORIUM PADA PEMBELAJARAN PRAKTIKUM MATERI PENCEMARAN AIR - Elvira Destiansari; Susy Amizera; Zainal Arifin (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2021)
This study aims to explain the results of the validation of the feasibility of virtual laboratory products in practicing water pollution materials. This research is a descriptive research and is also part of the development of a virtual laboratory on water pollution which consists of a preliminary study stage, a research planning stage and a product development stage. In this study, the data used were data at the develop preliminary product stage, namely product validation data. The results of material validation include 80.00% (sufficient) in the first validation and 88.57% (valid) in the second validation. The results of display validation include 77.14% (sufficient) in the first validation, 80.00% (sufficient) in the second validation, and 94.28% (valid) in the third validation. The results of language validation include 80.00% (sufficient) in the first validation and 93.33% (valid) in the second validation. Based on these results, the results of virtual lab development on water pollution material based on the results of material validation, appearance, and language constructs by a team of experts are categorized as valid and can be used for further processing.